Taxonomía numérica de la tribu Robinieae (Leguminosae, Papilionideae) en Cuba - Beyra Matos, Ángela (1995)
A taxonomic study of the Cuban species of the Robiniece (Fabacece, Fabo idea) tribe, in which numerical methods were used, is presented. Eighty characters and 164 states, using morphological and anatomical data, as well as those from foliar architecture were compared, in order to determine which of them are of higher importance in species diagnosis. Three phenograms were performed. Generally, the taxonomic conclusions at which we have arrived in this study show a remarkable coincidence with the results obtained by Lavin (1987, 1993) in his cladistic study of this tribe all over the world.